Effectiveness evaluation of quota payment for specific diseases under global budget: a typical provider payment system reform in rural China - Hao-miao Li; Ying-chun Chen; Hong-xia Gao; Yan Zhang; Liangkai Chen; Jing-jing Chang; Dai Su; Shi-han Lei; Di Jiang; Xiao-mei Hu (BMC, 2018)
Abstract Background Quota payment for specific diseases under global budget is one of the most typical modes of provider payment system reform in rural China. This study aimed to assess this reform mode from aspects of the total fee, structure of the fee and enrollees' benefits. Methods A total of 127,491 inpatient records from 2014 to 2016 were extracted from the New Rural Cooperative Medical Scheme (NRCMS) database in Weiyuan County, Gansu Province. Total fee, actual compensation ratio, out-of-pocket ratio, constituent ratio of the treatment fee, constituent ratio of the inspection and laboratory fee, and length of stay were selected as dependent variables. Both generalized additive models (GAMs) and multiple linear regression models were used to measure the change in dependent variables along with year. Results Prior to the adjustment of the compensation type, out-of-pocket ratio and length of stay decreased, while total fee, actual compensation ratio, constituent ratio of the treatment fee, and constituent ratio of the inspection and laboratory fee increased. After the compensation type was adjusted, the mean of the total fee increased rapidly in 2015 and remained stable in 2016. The mean length of stay increased in 2015 but decreased in 2016. A comparison of inpatients suffering from diseases covered by quota payments and those suffering from general diseases revealed that total fee, out-of-pocket ratio, and length of stay decreased and actual compensation ratio increased for the former, whereas the opposite was true for the latter. Constituent ratio of the treatment fee and constituent ratio of the inspection and laboratory fee increased for both samples, except for the constituent ratio of the inspection and laboratory fee of quota payment diseases in 2016, which did not change. Conclusions Quota payment for specific diseases under global budget had obviously positive effects on cost control in Weiyuan, Gansu. Considering the limited coverage of quota payment for diseases, the long-term effect of this reform mode and its replicability awaits further evaluation.